Edukasi Environment Pemanfaatan Sampah Plastik Untuk Bahan Tambahan Media Transplantasi Terumbu Karang Pada Peserta Didik Etnis Bajo Pada Pkbm Anak Pesisir Di Kampung Pelangi Kota Kendari - Wa Jali; Risfandi; Budiyanto (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to provide education and practical application of sustainable plastic waste management through the Edu Environmental program, utilizing plastic waste as an additional material for coral transplantation containers. The main focus of this program is the utilization of plastic waste as an additional material in the manufacture of coral transplantation containers, as an environmentally friendly marine ecosystem restoration effort. This activity was carried out in coastal areas that have the potential for coral reef damage due to human activities and plastic pollution. The implementation method includes socialization to PKBM Anak Pesisir Kota Kendari, to coastal communities, technical training in making transplantation media from a mixture of cement and plastic waste, as well as direct practice of planting transplantation containers in the sea. The results of the activity showed an increased understanding of PKBM students and the community regarding the importance of waste management and marine conservation, as well as initial success in the manufacture and installation of coral transplantation media from plastic waste additives. This program is expected to become an applicable environmental education model and encourage active community participation, especially PKBM students, in the preservation of marine ecosystems.